1986
DOI: 10.1073/pnas.83.7.2258
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific antibodies to quantitate the guanine nucleotide-binding protein Go in brain.

Abstract: We immunized rabbits with purified guanine nucleotide-binding proteins (G proteins) from bovine brain and obtained an antiserum, RV3, that reacts specifically with the a subunit (39 kDa) of a G protein of unknown function, termed Go, as well as with the P subunit (35 kDa) common to all G proteins. RV3 showed no crossreactivity with the a subunits of the stimulatory (Gj) or inhibitory (Gi) G proteins associated with adenylate cyclase, nor with that of the rod outer segment G protein, transducin. Immunoblots wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 16 publications
4
113
2
Order By: Relevance
“…However, with the purification of two pertussis toxin-sensitive Gproteins from bovine brain [21,22], and the subsequent demonstrations that these proteins were at least immunologically [22,23], if not functionally [24] distinct, it became apparent that a more selective means of assessing the molecular identity of pertussis toxin-sensitive G-proteins was required. The further demonstration that neither antisera which selectively identified the major form of Gr (Gil) or Go from brain were able to cross-react with the major pertussis toxin-sensitive substrate in human neutrophils [25] or in rat glioma cells [26] further added to the complexity of the system. cDNA cloning studies have now identified at least 6 potential G-protein a-subunit gene products which contain the characteristic signature of pertussis toxin substrates, that is, a cysteine residue located 4 amino acids from the C-terminus [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the purification of two pertussis toxin-sensitive Gproteins from bovine brain [21,22], and the subsequent demonstrations that these proteins were at least immunologically [22,23], if not functionally [24] distinct, it became apparent that a more selective means of assessing the molecular identity of pertussis toxin-sensitive G-proteins was required. The further demonstration that neither antisera which selectively identified the major form of Gr (Gil) or Go from brain were able to cross-react with the major pertussis toxin-sensitive substrate in human neutrophils [25] or in rat glioma cells [26] further added to the complexity of the system. cDNA cloning studies have now identified at least 6 potential G-protein a-subunit gene products which contain the characteristic signature of pertussis toxin substrates, that is, a cysteine residue located 4 amino acids from the C-terminus [4].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously characterised a polyclonal antiserum to rod transducin (CW6) [23] which cross-reacts with the major form of brain Gi (Gil), which on epitope mapping ap: peared to be directed against an epitope(s) within a very limited region of the protein [23,27]. This polyclonal antiserum shows little or no reactivity against the a-subunit of Gr2 [25,26] despite the fact that Gil and Gi2 are some 88% homologous at the primary sequence level. In this particular case one region (epitope) of the protein appeared to be immunodominant.…”
Section: Discussionmentioning
confidence: 99%
“…Gao belongs to the Gai family of G protein a subunits and shares about an 82% homology with Gai and is pertussis toxin sensitive (Neer et al, 1984;Sternweis and Robishaw, 1984;Van Meurs et al, 1987). The tissue distribution of Gao is quite interesting in that Gao is abundantly expressed in neuronal tissue (Gierschik et al, 1986). Intracellularly, Gao is found localized in the growth cones of neuronal tissue, suggesting a role for Gao in neuronal function (Nusse and Neer, 1996).…”
Section: E Ectors For Gao and Gai2mentioning
confidence: 99%
“…For that purpose the purified a subunits of transducin (a,) and bovine neutrophils (M,,) were used. The GTP-binding a subunit from bovine neutrophil membranes is a novel pertussis toxin substrate of 40 kDa which can be distinguished immunologically from bovine brain ai and a, [5]. The requirement of transducin fly or bovine brain By subunits for ADP-ribosylation of transducin a subunit is shown in Fig.…”
Section: Requirement Of Fly Subunits For Pertussis-toxin-catalyzed Admentioning
confidence: 99%